Exploring Kang Dedi Mulyadi's Strategic Leadership Model As Governor of West Java - Dwi Priyanto; Mhd. Fery Kusnadi; Johannes Johannes (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to explore the concept of strategic leadership through the leadership practices of Kang Dedi Mulyadi as Governor of West Java. The research approach used is descriptive qualitative with a literature study method, through searching various scientific sources and public policy documentation related to Dedi Mulyadi's leadership style. The analysis was conducted by comparing strategic leadership theories from various experts, such as Hughes, Yukl, and Suhardono, with the strategic practices and policies implemented by Dedi Mulyadi during his leadership. The results of the study show that Dedi Mulyadi's leadership is highly relevant to the characteristics of strategic leadership. This is reflected in his ability to formulate a long-term development vision, reprioritize pro-people budgets, implement innovative policies in the fields of infrastructure, education, and culture, and utilize social media as a means of public communication and social education. In addition, his leadership approach based on Sundanese local wisdom makes his public policies more humanistic, participatory, and rooted in the social values of the community. The conclusion of this study confirms that the strategic leadership practices implemented by Dedi Mulyadi are relevant to contemporary strategic leadership theory, particularly in terms of courage in decision-making, ability to manage change, focus on long-term results, and integration of cultural values into governance strategies. This leadership model can serve as an example of the application of contextual and locally-oriented strategic leadership in regional governance in Indonesia.